A római villa koncepciója ifjabb Plinius és Lucius Columella írásaiban = The concept of the Roman Villa according the writings of Pliny the younger and Lucius Columella - Ormos Bálint (Belvedere Meridionale, 2023)
For Pliny the Younger, who considered country villas to be comfortable homes, the profitability of landed estates was also important. And the link between estates and villas was taken for granted in the antique author’s own time, since ancient villas functioned not only as residences but also as estate centres. Pliny the Younger was mindful of the views of the agricultural writers who preceded him, such as Cato the Elder, Marcus Varro and Lucius Columella, on the purchase of an estate or, indeed, on the management of an estate. My aim in this paper is therefore to compare the contributions of Pliny the Younger and Lucius Columella, a close contemporary of his, on the Roman villa. The sources analysed in this paper are complemented by the findings of archaeological excavations.